Long and Short Run Relationship between Stock Market Development and Economic Growth in Nigeria - Anthony Olugbenga Adaramola; Modupe F. Popoola (Journal of Economics and Behavioral Studies, 2019)
We examined the long and short run association subsisting between stock market development (market capitalisation, value of transactions, number of deal and all share index), and Nigerian economic growth (RGDP) with quarterly data from 1986 to 2017. The Autoregressive Distributed Lag (ARDL) model is applied for the purpose of estimation. The ARDL bound test result revealed that all the indicators of market development exert positive effect on the RGDP in the short run. Further, all the indicators except number of deals, have direct and significant relationship with economic growth. Moreover, we find that market development causes economic growth. Consequently, we recommend a need for the implementation of policies and procedures capable of enhancing investors’ confidence and boosting market because of their perceived multiplier impacts on economic growth. Effort should also be focused on the enhancement of stock market size which in turn will provide the needed fund for investment and thus resulting in rise in the RGDP.